Re: Taking over of newly purchased land by the contractor - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reply on taking over of newly purchased land by the contractor of BRACU new campus project.